2021
DOI: 10.1111/ocr.12463
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the mandibular buccal shelf for orthodontic anchorage: Influence of side, gender and skeletal patterns

Abstract: Objectives: To evaluate bone height and thickness in the mandibular buccal shelf region and to compare differences between anatomical sites according to gender, side and vertical and sagittal skeletal patterns. Settings and sample population: Multislice computed tomography (MSCT) images of 94 subjects (51 females and 43 males) were previously obtained as part of preoperative planning for orthognathic surgery. Methods: Measurements were performed in three different regions of the mandibular buccal shelf: mesial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
(92 reference statements)
1
14
0
Order By: Relevance
“…In this study, the characteristics of the MBS were also evaluated according to sex and the side of the hermiarch, finding that there were no significant differences in both cases, which coincides with what was previously reported by other authors (14,15). Also, Farnsworth et al (24) observed that there was no difference in the cortical thickness of the mandibular alveolar bone between men and women.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the characteristics of the MBS were also evaluated according to sex and the side of the hermiarch, finding that there were no significant differences in both cases, which coincides with what was previously reported by other authors (14,15). Also, Farnsworth et al (24) observed that there was no difference in the cortical thickness of the mandibular alveolar bone between men and women.…”
Section: Discussionsupporting
confidence: 90%
“…Parinapucham et al (23) found that between hyperdivergent and normodivergent class III subjects, there were no differences for MBS cortical slope angle and bone thickness. While Aleluia et al (15) found that Class III hypodivergent subjects had greater bone thickness than the other groups.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The few studies that have evaluated bone availability at the IZC showed that its depth may vary from individual to individual 5,6 . Skeletal patterns are known to be related to different bone structures 15‐19 ; however, bone availability according to different vertical and sagittal patterns in the IZC at different angles has not been investigated. The purpose of this study was to determine the bone depth in the IZC area between the maxillary first and second molars in Class I, II and III subjects with different vertical patterns by means of tomographic images.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] The few studies that have evaluated bone availability at the IZC showed that its depth may vary from individual to individual. 5,6 Skeletal patterns are known to be related to different bone structures [15][16][17][18][19]…”
Section: Introductionmentioning
confidence: 99%